2010
DOI: 10.1242/jcs.062919
|View full text |Cite
|
Sign up to set email alerts
|

Focal-adhesion targeting links caveolin-1 to a Rac1-degradation pathway

Abstract: SummaryDirectional cell migration is crucially dependent on the spatiotemporal control of intracellular signalling events. These events regulate polarized actin dynamics, resulting in protrusion at the front of the cell and contraction at the rear. The actin cytoskeleton is regulated through signalling by Rho-like GTPases, such as RhoA, which stimulates myosin-based contractility, and CDC42 and Rac1, which promote actin polymerization and protrusion. Here, we show that Rac1 binds the adapter protein caveolin-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
109
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(119 citation statements)
references
References 62 publications
(82 reference statements)
9
109
1
Order By: Relevance
“…As a result of increased BRUCE degradation, there is a consequent decrease in cell proliferation (36). Interestingly, Cav-1 interacts with and regulates the polyubiquitinylation of active Rac1 (46). Rac1 is a member of the Rho-like GTPases and also involved in actin polymerization and protrusion and cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of increased BRUCE degradation, there is a consequent decrease in cell proliferation (36). Interestingly, Cav-1 interacts with and regulates the polyubiquitinylation of active Rac1 (46). Rac1 is a member of the Rho-like GTPases and also involved in actin polymerization and protrusion and cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…This small region shows striking sequence diversity among related GTPases, which has been linked to their differential localization to intracellular membranes, nuclear translocation as well as binding to regulatory-and effector-proteins. [12][13][14][15] In the early '90s, a series of studies established the functional importance of the HVR of Rac GTPases by focusing on its role in the activation of the NADPH oxidase complex. This complex was, at the time, already identified as an established Rac effector, responsible for production of reactive oxygen species in granulocytes.…”
Section: The Rac1 Hypervariable Region In Targeting and Signalingmentioning
confidence: 99%
“…Surprisingly however, we found that this correlated with an increase in total Rac1 protein levels. In other words, Caveolin1 regulates Rac1 expression, which is reflected in concomitant changes in the levels of GTP-bound Rac1 14 (Fig. 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All shRNA constructs were in the pLKO.1 vector backbone. shRNAexpressing lentiviral particles were prepared using HEK293T cells and the virus was transduced into SH-SY5Y cells as described previously (40). The knock down of TPP2 was confirmed by qPCR (see section RNA Isolation and Quantitative PCR) on the protein level by Western blotting, and TPP2 activity was measured using the AAF-AMC TPP2 activity assay (see section TPP2 Activity Assay).…”
Section: Methodsmentioning
confidence: 99%